Simulation analysis of IEEE 802.15.4 for wireless networked control systems - Afonso, José A. (2009)
The deployment of wireless networks in industrial environments can bring several advantages over their wired counterparts; however, the characteristics of the wireless channels pose challenges to the provisioning of quality of service (QoS) that are not seen in wired networks. This paper provides an analysis of how important QoS parameters, such as message delivery ratio, delay and energy consumption, vary as a function of the number of sensor nodes injecting traffic in IEEE 802.15.4 networks operating in unbeaconed mode. Results show that the peer-to-peer topology enables better performance than the star topology, under the same conditions, indicating that the former is a better option if centralized control is not required. The use of retransmissions increases significantly the reliability of the network; however, even a high number of retransmissions are not enough to provide full reliability when the channel is highly affected by errors. Results also show that presence of hidden nodes can severely degrade the performance of the network, while the reduction of the turnaround time can improve the performance.